Quasi-static magnetic measurements to predict specific absorption rates in magnetic fluid hyperthermia experiments - Coral, Diego Fernando (2014)
In this work, the issue on whether dynamic magnetic properties of polydispersed magnetic colloids modeled using physical magnitudes derived from quasi-static magnetic measurement can be extrapolated to analyze specific absorption rate data acquired at high amplitudes and frequencies of excitation fields is addressed. To this end, we have analyzed two colloids of magnetite nanoparticles coated with oleic acid and chitosan in water displaying, under a radiofrequency field, high and low specific heat power release. Both colloids are alike in terms of liquid carrier, surfactant and magnetic phase composition but differ on the nanoparticle structuring. The colloid displaying low specific dissipation consists of spaced magnetic nanoparticles of mean size around 4.8 nm inside a large chitosan particle of 52.5 nm. The one displaying high specific dissipation consists of clusters of magnetic nanoparticles of mean size around 9.7 nm inside a chitosan particle of 48.6 nm. The experimental evaluation of Néel and Brown relaxation times (∼10−10 s and 10−4 s, respectively) indicate that the nanoparticles in both colloids magnetically relax by Néel mechanism. The isothermal magnetization curves analysis for this mechanism show that the magnetic nanoparticles behave in the interacting superparamagnetic regime. The specific absorption rates were determined calorimetrically at 260 kHz and up to 52 kA/m and were well modeled within linear response theory using the anisotropy density energy retrieved from quasi-static magnetic measurement, validating their use to predict heating ability of a given polydispersed particle suspension. Our findings provide new insight in the validity of quasi-static magnetic characterization to analyze the high frequency behavior of polydispersed colloids within the framework of the linear response and Wohlfarth theories and indicate that dipolar interactions play a key role being their strength larger for the colloid displaying higher dissipation, i.e., improving the heating efficiency of the nanoparticles for magnetic fluid hyperthermia.